A retrospective review of the persistence on bDMARDs prescribed for the treatment of rheumatoid arthritis in the Australian population. (5th December 2017) - Jones, Graeme; Hall, Stephen; Bird, Paul; Littlejohn, Geoff; Tymms, Kathleen; Youssef, Peter; Chung, Eric; Barrett, Rina; Button, Peter
Abstract: Aim: To describe the persistence of biologic disease modifying anti‐rheumatic drugs (bDMARDs) in Australian rheumatoid arthritis (RA) patients, and assess the influence of methotrexate and other conventional DMARD (cDMARD) concomitant medications, and treatment line on bDMARD persistence and glucocorticoids usage. Method: RA patients, from the 10% Australian Medicare random sample, aged ≥18 for whom bDMARDs were dispensed were included. Individual sub‐cutaneous (SC) anti‐tumor necrosis factor‐α (anti‐TNFα) agents were combined as they were equivalent. Results: Data from 1230 patients were analyzed. For all patients the 12‐month persistence rates (based on Kaplan–Meier estimates) were 76% for intravenous (IV) tocilizumab, 63% abatacept (SC/IV), 61% SC‐anti‐TNFs and 36% IV‐infliximab. Persistence rates on first‐line bDMARDs were 79% (tocilizumab and abatacept), 64% (SC‐anti‐TNFs) and 13% (infliximab); rates were sustained for tocilizumab but dropped to 49% for abatacept and 51% for SC‐anti‐TNFs in the second‐line setting. Median treatment persistence was 40 months tocilizumab (95% CI: 30‐ND), 33 months abatacept (95% CI: 20‐ND); 22 months SC‐anti‐TNF (95% Cl: 18–27), and 4 months infliximab (95% CI: 2–13). Longer persistence was observed for SC‐anti‐TNFs and abatacept combined with methotrexate or other cDMARDs. For tocilizumab, persistence was robust with or without concomitant medications. The median oral glucocorticoid doses decreased from 4.1 mg/day (min 0, max 21) to 2.0 mg/day (min 0, max 17.3) over 2 years. Conclusions: Treatment persistence was longer on tocilizumab followed by abatacept then SC‐anti‐TNF therapy and was influenced by co‐therapy. Glucocorticoid dosage decreased with bDMARD use. This real‐world data highlights that persistence on bDMARDs differs according to biologics mode of action and co‐therapy.